Three-Dimensional Speckle Tracking Echocardiography Allows Detailed Evaluation of Left Atrial Function in Hypertrophic Cardiomyopathy-Insights from the MAGYAR-Path Study. - Domsik, Péter; Kalapos, Anita; Chadaide, Számi; Sepp, Róbert; Hausinger, Péter; Forster, Tamás; Nemes, Attila (Echocardiography, 2014)
Introduction Hypertrophic cardiomyopathy ( HCM) represents a generalized myopathic process affecting both ventricular and atrial myocardium. Reduced left atrial ( LA) function was demonstrated in HCM by different methods. Three-dimensional (3D) speckle tracking echocardiography ( STE) has just been introduced for the evaluation of LA. This study was designed to compare 3 DSTE-derived LA volumetric and strain parameters in HCM with healthy controls. Methods The study comprised 23 consecutive HCM patients (mean age: 48.5 ± 15.1 years, 14 men). Their results were compared to 23 age- and gender-matched healthy controls. Complete two-dimensional Doppler echocardiography and 3 DSTE have been performed in all cases. Results Calculated LA maximum (66.4 ± 20.4 mL vs. 36.0 ± 6.1 mL, P < 0.0001) and minimum (39.2 ± 19.1 vs. 16.0 ± 4.6 mL, P < 0.0001) volumes and LA volume before atrial contraction (53.6 ± 19.9 vs. 24.0 ± 6.2 mL, P < 0.0001) were significantly increased in HCM patients. Atrial stroke volumes respecting cardiac cycles proved to be increased, while emptying fractions were decreased in subjects with HCM. Mean global radial (−12.2 ± 6.7% vs. −19.6 ± 11.7, P < 0.05), longitudinal (26.5 ± 16.5% vs. 29.8 ± 12.1%, P < 0.05) and 3D strain (−6.1 ± 4.4% vs. −12.5 ± 10.2%, P < 0.05) proved to be significantly reduced in HCM patients as compared with matched controls. Conclusions Three-dimensional speckle tracking echocardiography allows detailed evaluation of LA (dys) function in HCM by volumetric and strain measurements.